2014
DOI: 10.1021/ja501252f
|View full text |Cite|
|
Sign up to set email alerts
|

Manganese Catalysts with Bulky Bipyridine Ligands for the Electrocatalytic Reduction of Carbon Dioxide: Eliminating Dimerization and Altering Catalysis

Abstract: With the goal of improving previously reported Mn bipyridine electrocatalysts in terms of increased activity and reduced overpotential, a bulky bipyridine ligand, 6,6'-dimesityl-2,2'-bipyridine (mesbpy), was utilized to eliminate dimerization in the catalytic cycle. Synthesis, electrocatalytic properties, X-ray diffraction (XRD) studies, and infrared spectroelectrochemistry (IR-SEC) of Mn(mesbpy)(CO)3Br and [Mn(mesbpy)(CO)3(MeCN)](OTf) are reported. Unlike previously reported Mn bipyridine catalysts, these Mn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
576
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(635 citation statements)
references
References 71 publications
42
576
3
4
Order By: Relevance
“…This carboxylate 44 can then be protonated and further reduced in a catalytic cycle as shown in Scheme 9. A Mn variant of this chemistry has also been reported [73] and specifically, the reduction of a (bpy)(CO) 3 Mn I CO 2 H was observed via IR-spectroelectrochemistry [74].…”
Section: Electrocatalytic Co 2 Reduction Via Metal Carboxylatesmentioning
confidence: 92%
“…This carboxylate 44 can then be protonated and further reduced in a catalytic cycle as shown in Scheme 9. A Mn variant of this chemistry has also been reported [73] and specifically, the reduction of a (bpy)(CO) 3 Mn I CO 2 H was observed via IR-spectroelectrochemistry [74].…”
Section: Electrocatalytic Co 2 Reduction Via Metal Carboxylatesmentioning
confidence: 92%
“…In particular, this change should affect the energy of the LUMO, the reduction potential, and catalytic activity. [23][24][25][26][27][28][29][30][31][32][33] Introducing steric bulk 23,25 to prevent unwanted reactions of the catalytic species, including dimerization as either Mn Mn, 9 or C(imino) C(imino) bound species, 21 whilst at the same time reducing the risk of increased overpotential is a challenging task. Molecular designs that allow for steric and electronic effects to be decoupled are required.…”
Section: Chartmentioning
confidence: 99%
“…23 Indeed, it has recently been shown that the use of bipyridines incorporating bulky groups in the 6,6 -positions 24,25 (or, another bulkier heterocyclic ligand 26 ) largely inhibits dimerization in the catalytic cycle. The result is the formation of the stable 5-coordinate anion via the two-electron transfer (ECE) at the first cathodic wave.…”
mentioning
confidence: 99%
“…solar fuels | CO 2 reduction | electrochemistry | catalysis | contemporary energy challenges T he reductive conversion of CO 2 to CO is an important issue of contemporary energy and environmental challenges (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Several low-oxidation-state transition metal complexes have been proposed to serve as homogeneous catalyst for this reaction in nonaqueous solvents such as N,N'-dimethylformamide (DMF) or acetonitrile (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%